Relevansi Metode Pembelajaran Pendidikan Agama Islam Terhadap Karakteristik Siswa Gen Z Pada Tujuan Kurikulum - Muhammad Arif Luthfi; Alfauzan Amin; Zubaedi Zubaedi; Rohimin Rohimin; Destriani Destriani (Universitas Muhammadiyah Mataram, 2026)
Digital transformation in Islamic Religious Education (IRE) has encouraged various learning innovations adapted to Generation Z characteristics; however, the alignment between digital pedagogy and the holistic goals of the IRE curriculum remains challenging. This study aims to analyze the relevance, pedagogical approaches, and alignment of digital Islamic pedagogy with the objectives of the IRE curriculum through a Systematic Literature Review (SLR). The study employed PRISMA 2020 guidelines by reviewing articles indexed in Scopus and SINTA from 2021–2026. A total of 28 eligible articles were analyzed using thematic synthesis. The findings reveal that digital Islamic pedagogy is still dominated by technology-based approaches focusing primarily on taklim or cognitive dimensions. Its alignment with the IRE curriculum tends to be partial, as affective and spiritual dimensions remain insufficiently accommodated. Therefore, the development of digital pedagogical designs integrating taklim, tarbiyah, and takdib holistically is urgently needed.